Race-religion constellation: An argument for a Trans-Atlantic Interactive-Relational Approach - Tembo, Josias (Critical research on religion, 2022)
In this article, I argue that a trans-Atlantic account of the constellations of race and religion demands that we understand racist thinking to be constituted by complex conceptual formations and relations. The failure to identify the conceptual complexity and interactive relations in racist thinking has led to universalist and exclusionary definitions of racist thinking and limited conceptions of the constellations of race and religion. Because the supposed universal definitions of racist thinking are formulated from particular regions of the trans-Atlantic, it has led to the masking and rejection of other formations of racist thinking from other regions of the trans-Atlantic. To avoid this, this article proposes a Trans-Atlantic Interactive and Relational Approach (TAIRA) that can help us to continue unmasking and understanding the trans-Atlantic connections between race and religion.